Funder Requests A4NH Inputs into the Direction of a Major Development Investment Strategy to Mitigate any Unintended Negative Consequences on Human Health in West Africa - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
In Africa, a child dies of malaria every two minutes. Ricefields are an important breeding place for mosquitoes. Recent work by A4NH has confirmed that the introduction of rice brings more malaria to local residents; hence rice intensification may be an obstacle to malaria elimination. In 2020, a meeting was convened to bring together Japanese agronomists and health experts to discuss the implications of A4NH research for their plans to support a major expansion of irrigated rice in Africa.